2016
DOI: 10.1158/1535-7163.mct-15-0566
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glycogen Synthase Kinase-3 Inhibitor Optimized for Acute Myeloid Leukemia Differentiation Activity

Abstract: Standard therapies used for the treatment of acute myeloid leukemia (AML) are cytotoxic agents that target rapidly proliferating cells. Unfortunately, this therapeutic approach has limited efficacy and significant toxicity and the majority of AML patients still die of their disease. In contrast to the poor prognosis of most AML patients, most individuals with a rare subtype of AML, acute promyelocytic leukemia, can be cured by differentiation therapy using regimens containing all-trans retinoic acid. GSK3 has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
20
0
7
Order By: Relevance
“…The treatment of this disease is mainly induced differentiation therapy. [24][25][26][27][28][29] The cell cycle is a series of events that leads to cell division and replication.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of this disease is mainly induced differentiation therapy. [24][25][26][27][28][29] The cell cycle is a series of events that leads to cell division and replication.…”
Section: Discussionmentioning
confidence: 99%
“…100 Pentose phosphate pathway activity, cysteine import, GSH, and thioredoxin production represent processes that can be fine-tuned have been considered for the treatment of myeloid leukemia. 104,105 Further insight into the signaling pathways, which render B cells susceptible to GSK3 inhibition, could provide a rationale to extend the use of GSK3 inhibitors to B cell-derived malignancies or improve disease stratification. Lastly, since it is becoming increasingly apparent that B cell metabolism and function are not only regulated by intracel-…”
Section: Con S Equen Ce S Of D Is Rup Ted Me Tabolic Homeos Ta S Ismentioning
confidence: 99%
“…Leukaemia cell differentiation is a key factor to evaluate the malignancy. Previous studies put forward many targets, regulation of which was directly correlated with the leukaemia cell differentiation . On the basis of these reports, our study firstly shows that regulation of HoxA9 expression was able to control the HL‐60 and MOLT‐3 cell differentiation (Figure ).…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies put forward many targets, regulation of which was directly correlated with the leukaemia cell differentiation. [16][17][18] On the basis of these reports, our study firstly shows that regulation of HoxA9 expression was able to control the HL-60 and MOLT-3 cell differentiation ( Figure 5). This is a novel finding that HoxA9 was correlated with leukaemia cell differentiation, further demonstrating that this gene is an FIGURE 7 Xenograft experiment indicated that HoxA9 silencing reduced the tumour malignancy.…”
Section: Discussionmentioning
confidence: 64%